1996
DOI: 10.1007/bf00033125
|View full text |Cite
|
Sign up to set email alerts
|

Photoconversion of long-wavelength protochlorophyll native form Pchl 682/672 into chlorophyll Chl 715/696 in Chlorella vulgaris B-15

Abstract: By spectral methods, the final stages of chlorophyll formation from protochlorophyll (ide) were studied in heterotrophic cells of Chlorella vulgaris B-15 mutant, where chlorophyll dark biosynthesis is inhibited. It was shown that during the dark cultivation, in the mutant cells, in addition to the well-known protochlorophyll (ide) forms Pchlide 655/650, Pchl(ide) 640/635, Pchl(ide) 633/627, a long-wavelength protochlorophyll form is accumulated with fluorescence maximum at 682 nm and absorption maximum at 672 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The difference in PSI-specific fluorescence observed at 294 K between P. kessleri and maize in our analysis seems to correlate well with the different fluorescence peak positions observed for PSI at cryogenic temperatures below 100 K (see Introduction). [19][20][21][22][23][24]26 However, it should be noted that the peaks of difference and ratio spectra showing the PSI-specific fluorescence component are possibly different from the whole PSI spectrum in chloroplasts. For example, because of the subtraction of the pulsed-laserinduced spectra from the CW-laser-induced spectra, it is likely that the difference spectra in Figure 1A, C, and E are more redshifted than the whole PSI fluorescence.…”
Section: ' Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in PSI-specific fluorescence observed at 294 K between P. kessleri and maize in our analysis seems to correlate well with the different fluorescence peak positions observed for PSI at cryogenic temperatures below 100 K (see Introduction). [19][20][21][22][23][24]26 However, it should be noted that the peaks of difference and ratio spectra showing the PSI-specific fluorescence component are possibly different from the whole PSI spectrum in chloroplasts. For example, because of the subtraction of the pulsed-laserinduced spectra from the CW-laser-induced spectra, it is likely that the difference spectra in Figure 1A, C, and E are more redshifted than the whole PSI fluorescence.…”
Section: ' Discussionmentioning
confidence: 99%
“…In this work, we have examined the generality of PSI-specific fluorescence enhancement with CW NIR laser excitation in the case of a green alga (Parachlorella kessleri or Parachlorella Krienitz, previously classified in the genus Chlorella ) that show a PSI-specific fluorescence peak at 715−725 nm at 77 K. This fluorescence wavelength is at least about 10 nm blue-shifted when compared with those observed in higher plants, which appear at 735−740 nm. ,,, It is important to establish whether the enhancement of PSI-specific fluorescence with CW NIR laser excitation at room temperature reflects the fluorescence peak wavelengths at cryogenic temperatures. We have also attempted to induce artificial red Chl inside of or in close proximity to the thylakoid membrane to study if its fluorescence can be readily observed under CW NIR laser excitation.…”
Section: Introductionmentioning
confidence: 99%